An Interpersonal Psychotherapy Approach to Counseling Student Athletes: Clinical Implications of Athletic Identity. Issue 2 (3rd July 2013) - Heird, Emily Benton; Steinfeldt, Jesse A.
<x xml:space="preserve">Abstract</x> Research has shown that disruptive circumstances in an athlete's career (temporary injury, permanent injury, retirement) can pose significant difficulties, especially if the athlete has developed a salient athletic identity at the expense of a multidimensional self‐concept. The authors present an interpersonal psychotherapy approach to case conceptualization with student athletes that can be effective because of its brief nature and focus on grief, role transitions, interpersonal deficits, and interpersonal disputes.